Determination of beam quality correction factors for the Roos plane-parallel ionisation chamber exposed to very high energy electron (VHEE) beams using Geant4. (21st March 2022) - McManus, M; Romano, F; Royle, G; Botnariuc, D; Shipley, D; Palmans, H; Subiel, A
Abstract: Detailed characterisation of the Roos secondary standard plane-parallel ionisation chamber has been conducted in a novel 200 MeV Very High Energy Electron (VHEE) beam with reference to the standard 12 MeV electron calibration beam used in our experimental work. Stopping-power-ratios and perturbation factors have been determined for both beams and used to calculated the beam quality correction factor using the Geant4 general purpose MC code. These factors have been calculated for a variety of charged particle transport parameters available in Geant4 which were found to pass the Fano cavity test. Stopping-power-ratios for the 12 MeV electron calibration beam quality were found to agree within uncertainties to that quoted by current dosimetry protocols. Perturbation factors were found to vary by up-to 4% for the calibration beam depending on the parameter configuration, compared with only 0.8% for the VHEE beam. Beam quality correction factors were found to describe an approximately 10% lower dose than would be originally calculated if a beam quality correction were not accounted for. Moreover, results presented here largely resolve unphysical chamber measurements, such as collection efficiencies greater than 100%, and assist in the accurate determination of absorbed dose and ion recombination in secondary standard ionisation chambers.